DAYA DUKUNG LAHAN DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) GOMBONG (Carrying capacity of land in Forest Area for Specific Purpose (KHDTK) Gombong) - Nur Ainun Jariyah (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2018)
ABSTRACTPopulation growth has an impact on increasing the need for land to fulfill people’s food, thus it may decrease the carrying capacity of land. Therefore, a study has been conducted to evaluate the carrying capacity of the land to meet the needs of the local community at Forest Area for Specific Purpose (KHDTK) Gombong, Kebumen District, Central Java. Secondary data collection was including population, land area, productivity and price from agriculture, plantation, forestry, livestock and fishery, rice prices at producer level. Another secondary data collection was collected from Central Bureau of Statistics of Kebumen, forest district service, districts and villages. Data were analyzed using a descriptive quantitative method by calculating the supply and demand of land to know carrying capacity of the land. The result of this research showed that the availability land in KHDTK Gombong was 68,559.72 ha while the required land was 101,909.56 ha, thus experiencing a deficit of - 33,349.84 ha. The deficit condition in KHDTK Gombong can be fulfilled from Kebumen regency that has a surplus or cooperate with other regions. This condition makes the attention of the local government to overcome KHDTK Gombong such as increase land availability, land conversion towards other more profitable business, land intensification with new technology and land conservation.Keywords: land supply; land demand; KHDTK Gombong; deficit ABSTRAKPertambahan jumlah penduduk berdampak pada peningkatan kebutuhan akan lahan untuk memenuhi pangan sehingga dikhawatirkan akan menurunkan daya dukung lahan. Untuk itu telah dilakukan penelitian yang bertujuan mengetahui daya dukung lahan di Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Gombong dalam mencukupi kebutuhan masyarakat sekitar. Pengumpulan data sekunder meliputi: jumlah penduduk, luas lahan, produktivitas, dan harga produk (pertanian, perkebunan, kehutanan, peternakan, dan perikanan), serta harga beras di tingkat produsen. Pengumpulan data sekunder juga dilakukan di Badan Pusat Statistik Kabupaten Kebumen, dinas kehutanan, kecamatan, dan kelurahan. Data dianalisis dengan menggunakan deskriptif kuantitatif dengan menghitung ketersediaan (supply) dan kebutuhan (demand) lahan untuk mengetahui daya dukung lahan. Hasil penelitian menunjukkan bahwa ketersediaan lahan di KHDTK Gombong sebesar 68.559,72 ha dan kebutuhan lahan sebesar 101.909,56 ha, sehingga mengalami defisit sebesar -33.349,84 ha. Kondisi yang defisit di KHDTK Gombong dapat dipenuhi dari Kabupaten Kebumen yang mengalami surplus meskipun tidak menutup kemungkinan bekerjasama dengan wilayah lain. Daya dukung lahan di KHDTK Gombong dapat ditingkatkan dengan meningkatkan ketersediaan lahan, konversi lahan ke arah usaha lain yang lebih menguntungkan, intensifikasi lahan dengan teknologi baru, dan konservasi lahan.Kata kunci: ketersediaan lahan; kebutuhan lahan; KHDTK Gombong; deficit